The Evolution of Southeast Asian Regionalism: Security, Economic Development and Foreign Power Support for Regional Initiatives, 1947-77 - Thompson, Sue (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
Policy objectives for Southeast Asian regionalism had been evolving since the end of the Second World War. Economic development viewed as essential for establishing peace and stability in Southeast Asia and the links between development and security were evident in the elaboration of the Association of Southeast Asian Nations (ASEAN). Also evident was the second-line support provided by external powers. While ASEAN was a regional initiative that came out of the Bangkok talks to end Confrontation, Western governments had been formulating regional cooperation policies in Southeast Asia decades prior. Economic development viewed as essential for containing communist influence and preventing internal insurgencies in the region. Growth and prosperity would come through regional development programs with external support. This would then expand to some form of collective security led by the Southeast Asian nations themselves. Regionalism viewed as one way of providing economic assistance to newly independent nations without the appearance of foreign interference in regional affairs. Therefore, the evolution of Southeast Asian regionalism was a combined effort of foreign power support for Asian initiatives throughout the economic development with the aim to provide security during the political transformation of the region from the post-war period into the early years of ASEAN and the aftermath of the war in Vietnam.